Mastering Microsoft Dynamics 365 Business Central : discover extension development best practices, build advanced ERP integrations, and use DevOps tools - Demiliani, Stefano; Tacconi, Duilio (Packt Publishing, 2019)
Mastering Microsoft Dynamics 365 Business Central is a comprehensive solution which will help you in managing end-to-end business requirements with its features to connect to your financials, sales, service, and operations to streamline business processes. This book will help you in advancing with developing the solutions for your customers ...